AN ANALYSIS OF CODE SWITCHING AND FACTOR MOTIVATION IN NESSIE JUDGE VLOG - Dida Nurul Fadillah; Aseptiana Parmawati (IKIP Siliwangi, 2020)
The phenomena of language is a phenomena that is currently happening in Indonesia as well as the language and style of language in communication, mix or switch into another language especially English and it can be called Code Switching. Many sources of media that we can use to see how code switching is, and one of the flatfrom is Vlog. Based on the introduction, this research tries to analyze a code switching, the main is the types, and analyze a factor motivation by using descriptive qulitative method. The aims of this article are to find out the types of code switching from her utterances in vlog using code switching and the factor motivation that influenced in doing code switching. The factor motivating that influenced for Nessie Judge do a code switching in her vlog on her daily communication because of social and lingustic factors or types. Based on the finding of data that the writer analyze from Nessie Judge’s utterance in her vlog, the most types of code switching that in Nessie Judge utterances is Intersentential type